![Исидор](https://sproshu.net/uploads/ava/1/ava4226.jpg)
Исидор
6 год назад
(x-4)(x+3)+(x-2)(x+3) = 0
![](https://store.sproshu.net/2/9c98cdcc8c.jpg)
ОТВЕТЫ
![Феофилакт](https://sproshu.net/uploads/ava/4/ava6101.jpg)
Феофилакт
Jun 30, 2019
(х^2+3х-4х-12)+(х^2+3х-2х-6)=0 раскрываем скобки
х^2+3х-4х-12+х^2+3х-2х-6=0
х^2-18=0
D=0^2-4*2*(-18)=0+144=144 √D=12
x1= 0+12/2*2=12/4=3
x2=0-12/2*2=-12/4=-3
х^2+3х-4х-12+х^2+3х-2х-6=0
х^2-18=0
D=0^2-4*2*(-18)=0+144=144 √D=12
x1= 0+12/2*2=12/4=3
x2=0-12/2*2=-12/4=-3
(x+3)×(x-4+x-2)=0
(x+3)×(2x-6)=0
2x²-6x+6x-18=0
2x²-18=0
2x²=18
x²=9
x=+-3
(x+3)×(2x-6)=0
2x²-6x+6x-18=0
2x²-18=0
2x²=18
x²=9
x=+-3
208
Смежные вопросы: